2010
DOI: 10.5152/ttd.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disorders and Occupational Accident in Shift Work Nurses

Abstract: Objective: This study aimed to investigate the prevalence of symptoms of sleep related breathing disorders in shiftwork nurses and to evaluate relationship between occupational accident and the symptoms. Material and Method:Data of 410 nurses was evaluated. A questionnaire was administered to get information on their socio-demographic data, presence of witnessed apnea during sleep, the prevalence of snoring, excessive daytime sleepiness and frequency of other symptoms and having any occupational accident. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In the literature, insufficient sleep durations caused by working in shifts and circadian rhythm disorders have been reported to cause excessive daytime sleepiness (7) . In two similar studies, sleeplessness problems in nurses working in night shifts was reported (27) , while the inclination for sleep during work was found to be greater in workers working in shifts compared to those who worked during the day (9) . In this study, the ESS scores were higher in the nurses working in shifts.…”
Section: Sleep Status and Occupational Accidentsmentioning
confidence: 78%
See 3 more Smart Citations
“…In the literature, insufficient sleep durations caused by working in shifts and circadian rhythm disorders have been reported to cause excessive daytime sleepiness (7) . In two similar studies, sleeplessness problems in nurses working in night shifts was reported (27) , while the inclination for sleep during work was found to be greater in workers working in shifts compared to those who worked during the day (9) . In this study, the ESS scores were higher in the nurses working in shifts.…”
Section: Sleep Status and Occupational Accidentsmentioning
confidence: 78%
“…Although the daily sleep durations of the participants, who had difficult employment conditions, seemed sufficient, the fact that a large majority (65.7%) had a desire to sleep during the day can be seen as an important problem. Excessive daytime sleepiness is another important symptom of sleep disorders (9) . The Epworth Sleepiness Scale is a subjective tool for measuring sleepiness.…”
Section: Sleep Status and Occupational Accidentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The most important of these problems is the problem of sleep. It was found that there was a significant relationship between sleepiness and work accidents [3]. Working time at the workplace and the frequency and duration of rest periods are highly influential on the physical and mental balance of employees [4].…”
mentioning
confidence: 99%